Perilaku Sehat Cegah Stunting Melalui Modul Emotional-Demonstration (Emo-Demo) - Purwanti, Aisyah Tri; Fidia, Andryana Martha; Pratama, Dikri Aulia; Wenda, Novita; Novita, Tri Liana; Ningtyias, Farida Wahyu; Adi, Dhuha Itsnanisa (Jurnal SOLMA, 2025)
Background: Data from the Sumenep District Health Office contained in Soesanti's research (2019) states that the prevalence of short and very short toddlers in 2018 shows a fairly high rate of 34.3%. Inappropriate parenting, namely the lack of intake of protein sources such as eggs, sea fish and chicken both in quality and quantity, is one of the factors causing stunting in Sumenep District. Education with the Emo-Demo method that touches the emotional side of the target is effective in increasing knowledge and leading to behavior change. The purpose of education with the Emo-Demo method is to provide knowledge related to healthy behavior to prevent stunting. Methods: Conduct health promotion activities using the Emo-Demo method for mothers in the Flamboyant Posyandu area in East Jepun Hamlet, East Lenteng Village, Lenteng District, Sumenep Regency. The implementation was carried out on Wednesday, December 23, 2020 at 15.30 WIB to 7 pregnant women and toddlers as the target of the activity. Results: The results of Emo-Demo activities showed an increase in knowledge of 42.5%. This shows that Emo-demo activities can be said to be effective in increasing target knowledge. Conclusion: Emo-Demo activities on healthy behaviors to prevent stunting can be given to the right targets such as pregnant women and toddlers so that the messages contained in Emo-Demo can be conveyed.